Aplicação de sensores à fibra óptica no monitoramento térmico de painel fotovoltaico - Santolin, Edson Antonio (2016)
This paper has been studying the applications of Bragg gratings in optical fibers, as sensors for thermal mapping and monitoring on photovoltaic panel surface which was installing in an open environment. We also analyzed the ability of optical fibers sensors to detect electrical anomalies in the panel, which are manifested by the changes in its temperature. Because it was pioneering in study of optical fiber application into photovoltaic panel, this paper's objective is compare the results between this technology and the other techniques for temperature measurements, for example when are used the PT100 sensors or infrared camera. Assays were performed using a photovoltaic panel that is installed in an open environment, its temperature changes were measured by a total of 27 optical fiber sensors installed on the front surface. During the tests, the environmental conditions of temperature, level of solar radiation and wind speed, were monitored. The results demonstrate the potential use of Bragg gratings in optical fiber for detecting thermal fluctuations caused by environmental factors or by heating the cells.